Oral Presentations Abstracts: THE VALUE OF PRIVACY IN SMART DEMENTIA CARE: EMPIRICAL AND ETHICAL - SCHWEDA, Mark; BUHR, Eike (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 To protect people with dementia (PwD) from harm, smart technologies are developed to monitor their everyday life and activities and to intervene if necessary. For example, such technologies comprise wearables or video sensors that rely on human-machine interaction. In the ethical and political debate, such monitoring devices are usually discussed under the aspect of privacy. Generally, privacy is understood as a right that entails an active and deliberate control over one’s own decisional, informational and topological concerns. In short, the right to privacy is closely connected to personal autonomy. However, this conception raises problems when applied to PwD. Due to cognitive decline, they lose the ability to actively control their own concerns so that it might seem as though they also forfeit their right to privacy. Yet, this contradicts common moral intuitions as well as empirical studies which suggest that PwD value privacy as an important part of their quality of life (Dichter 2016). Against this backdrop, our contribution explores the “value of privacy” (Rössler 2001) in the context of smart dementia care. First, we determine the limits of common understandings of privacy when applied to PwD. Starting from empirical studies on the subjective experience of PwD, we then discuss how the moral significance of privacy can be spelled out without tying it explicitly and exclusively to autonomy. On this basis, we discuss preconditions of privacy for PwD in smart dementia care settings, formulating recommendations for future technology development and smart dementia care.